Thyroid status, but not insulin status, affects expression of avian uncoupling protein mRNA in chicken - Collin, A.; Taouis, M.; Buyse, J.; Ifuta, N. B.; Darras, V. M.; Van As, P.; Malheiros, R. D.; Moraes, VMB; Decuypere, E. (Amer Physiological Soc, 2003)
The aim of this study was to investigate the hormonal regulation of the avian homolog of mammalian uncoupling protein (avUCP) by studying the impact of thyroid hormones and insulin on avUCP mRNA expression in chickens (Gallus gallus). For 3 wk, chicks received either a standard diet (control group), or a standard diet supplemented with triiodothyronine (T-3; T3 group) or with the thyroid gland inhibitor methimazole (MMI group). A fourth group received injections of the deiodinase inhibitor iopanoic acid (IOP group). During the 4th wk of age, all animals received two daily injections of either human insulin or saline solution. The results indicate a twofold overexpression of avUCP mRNA in gastrocnemius muscle of T3 birds and a clear downregulation (-74%) in MMI chickens compared with control chickens. Insulin injections had no significant effect on avUCP mRNA expression in chickens. This study describes for the first time induction of avUCP mRNA expression by the thermogenic hormone T3 in chickens and supports a possible involvement of avUCP in avian thermogenesis.
Keywords: thyroid hormones; thermogenesis; muscle